From 1917 to 1937: The Muftī, the Turkologist, and Stalin’s Terror - Kemper, Michael (Die Welt des Islams, 2017)
The Tatar religious scholar Rizaeddin Fakhreddinov (1859-1936) is well-known as a Jadīd publicist and historian, but his time as qāḍī and muftī of Soviet Russia (1918-36) is still unexplored. Muftī Fakhreddinov witnessed the Bolsheviks’ gradual elimination of all Islamic community life. In 1935 he considered saving his personal archive from destruction by transferring it to the Institute of Oriental Studies in Leningrad, the director of which, Turkologist Aleksandr N. Samoilovich (1880-1938), enjoyed his trust. But Fakhreddinov passed away in 1936, and in 1937 the NKVD constructed a group case against Muslim historians and philologists into which Samoilovich and Fakhreddinov’s sons were also drawn. After Stalin’s death in 1953, the “rehabilitation” of these victims of state terror was slow and selective, and scholarship on Islam in Russia was severely crippled. Only the late 1980s and the 1990s brought a window of opportunity for revisiting the Bolsheviks’ destruction of the secular and Islamic elites.